Morfologia foliar e controle de plantas daninhas em função do sombreamento - Hoffmann, Daniela (2007)
Grain development and yield are influenced by several factors, including weed invasion. Currently, the use of herbicides is the major method for weed control. Leaves are the main route of postemergence herbicide absorption; however, they are a complex structure that imposes several barriers to herbicide movement and penetration. This study hypothesizes that shading, changes leaf morphology, facilitating herbicide uptake, and thus allowing for the use of lower herbicide doses. The aim of this study was to assess the effect of shading on leaf morphology, as well as on the efficacy of weed control in soybean. Increased shading enhances plant height and reduces above-ground dry matter accumulation, changes and the number of cellular layers. Lower doses allow better weed control in shaded plants than in unshaded ones. Grain yield and the number of pods and seeds per plant increase with higher herbicide doses and with the presence of straw residues. In conclusion, shading changes leaf morphology and the number of cellular layers, and increase grain yield and the number of pods and seeds per plant